Cơ quan thông tin-thư viện ngành ở Việt Nam - Phạm, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Outlines the state of the art and legal framework of specialized library and information institutions in Vietnam; makes clear the limitation of their technical and material infrastructure, funding and human resources, information capacity, management and direction quality, as well as cooperation relations; puts forward some recommendations to overcome the weakness.